Evaluation of syndesmosis reduction after removal syndesmosis screw in ankle fracture with syndesmosis injury - Farzad Amouzadeh Omrani; Gholamhosein Kazemian; Sohrab Salimi (Advanced Biomedical Research, 2019)
Background: Ankle fracture–dislocation with a syndesmotic injury has been treated with syndesmotic screw fixation. There are little evidences about the safety and efficacy of syndesmotic screw removal on the syndesmotic malreduction. This study aimed to evaluate the effects of syndesmotic screw removal of distal attachment of the fibula and tibia bones on the syndesmotic reduction and also impact of syndesmotic screw removal on the final functional score of ankle joint. Materials and Methods: Patients who underwent syndesmotic screw fixation for diagnosed syndesmosis injury during internal fixation surgery for ankle fractures from April 2017 to March 2018 were assessed for enrollment in our study. During open reduction and internal fixation for ankle fracture, existence of syndesmosis injury was evaluated using the Cotton test and external rotation stress test. Appropriate rehabilitation including short leg cast and nonweight bearing have been accomplished for a duration 12 weeks before removing of syndesmotic screws. At 12 weeks, screws were removed. After 1-month weight bearing, bilateral axial computed tomography (CT) scan and single-leg weight-bearing X-ray for injured ankle were obtained. Results: Of all 60 participants, 42 cases (70%) were male and 18 cases (30%) were female. Postoperative ankle radiographies were normal except one case with increased medial clear space. It was interesting findings that from total 60 cases, 18 patients (30%) had evidence of syndesmosis malreduction on postoperative initial CT scan, and after removing of syndesmotic screws (12 weeks) and a period of weight bearing and rehabilitation (4 weeks), there is evidence of appropriate reduction in 13 cases (of 18 patients [72.2%]) on final CT scans.Conclusion: Syndesmotic screw removal and weight bearing may be advantageous to achieve final anatomic reduction of the syndesmosis. Syndesmotic screw removal at appropriate time could not improve foot functional outcomes; however, more studies with the larger sample size are required to confirm the results of the study.